Monetary policy reaction function and transmission effectiveness: evidence from full-fledged inflation targeting Sub-Saharan African countries - Iddrisu, Abdul-Aziz (My University, 2020)
The relevance of monetary policy rules in providing a framework for policy coherence, stability and optimality has long been acknowledged. The eventual impact of optimal monetary policy response on the real economy, dependent on the effectiveness of the channels of transmission of monetary policy impulses, is even more crucial. Much as empirical literature on monetary policy rules and transmission effectiveness abound, substantial limitations still persist. The continuous focus on linear policy rules in the face of observed asymmetry in monetary policy behaviour; the dilemma and constraints posed to monetary policy responses by rising public debt levels; the direct approach to transmission channel exposition that is far from theoretical prescription; the assumption of homogeneity in prices that confront all agents in an economy which is far from reality; and the egregious neglect of the stabilizing effect of monetary policy on food prices despite the colossal role of the latter in the overall inflation dynamics of developing and poor economies are important research gaps in the monetary policy rule and transmission literature. Meanwhile, appropriate policy characterization and succinct comprehension of the dynamics of transmission are critical in shaping optimal and welfare-enhancing monetary policy. This thesis is centred on four thematic areas, with each considering an important gap (as a distinct essay) relating to monetary policy characterization and transmission. The first essay considers a nonlinear Taylor rule for the characterization of the monetary policy responses of the only two full-fledged inflation targeting central banks in Africa (Bank of Ghana and the South African Reserve Bank) and whether the said responses are constrained by rising public debt levels. With the aid of the sample splitting and threshold estimation technique, we find asymmetric reaction to inflation and output gaps when inflation falls below or exceeds our estimated optimal thresholds of 16.4% and 5.2% for Ghana and South Africa respectively, with the South African Reserve Bank being relatively more aggressive in its response to inflation gap above the threshold. The Bank of Ghana is not responsive to output gap on either side of the threshold. Importantly, we find that the monetary policy behaviour of the two central banks is far from the linear characterization and parametrization so common in the literature. For Ghana, we question the logic behind the prevailing upper and lower bounds given the evidence to the contrary. In respect of debt constraint on monetary policy, our estimated threshold level of debt to GDP ratio for Ghana and South Africa are respectively 35.1% and 33.7%. For Ghana, although policy response to inflation gap exhibits relative aggression above the estimated debt to GDP threshold of 35.1%, the extent of response is woefully disproportionate, a key indication of debt constraint and inflation accommodation. For South Africa, we find that the policy response in the low debt regime to inflation gap is negative, on the back of accommodative monetary policy when inflation exceeded the upper limit of the announced target in the midst of challenging growth path. Although the response to inflation gap in the high debt regime is positive, it is substantially constrained. The extent to which monetary policy decisions exact the desired results in the real economy is essentially a function of the effectiveness of the channels of monetary policy transmission. Comprehending the architecture and dynamics of the workings of these channels is thus critical for the monetary policymakers, as it helps them to determine how and when their decisions eventually impact the real economy and the nature of instruments to adopt. We revisit, in the second essay, the workings of the interest rate and bank lending channels in an indirect and systematic approach anchored on the theoretical prescriptions and a major departure from empirical literature. With the aid of the three stage least square technique (3SLS) in a system of equations, we find that the interest rate and the lending channels are operative in Ghana and South Africa. We find that whiles the lending channel is more effective relative to the interest rate channel in South Africa, the reverse is the case in Ghana. The fact that different regions/provinces have different economic structures and endowments is an ample reason to expect that price developments in these regions/provinces and their responses to monetary policy would necessarily be distinct. Literature has largely assumed homogeneity in the prices that confront economic agents with dire consequences for welfare. The third essay, therefore, looks at asymmetric effect of monetary policy on regional and provincial inflation in Ghana and South Africa. Using wavelet-based quantile regression for the first time in this strand of the literature, we provide a multi-layered asymmetric exposition on regional inflation-monetary policy relationship. We find that regions/provinces respond differently to changes in monetary policy. For Ghana, we find that for Central, Eastern, Greater Accra, Northern and Western regions, a restrictive monetary policy exacts mixed effect. Whiles monetary policy delivered stability across distinct quantiles in some scales, it fueled inflationary momentum in other scales, especially the higher scales or longer horizons. The responses are also distinct across scales and quantiles for each of the regions and across regions. In the case of Ashanti, Brong Ahafo and Volta regions, we find that a restriction in monetary policy only destabilizes prices across quantiles and in distinct scales. For South Africa, we find that whiles restrictive monetary policy delivers stability in the prices of Gauteng, Mpumalanga and North West provinces, it is destabilizing for prices in Eastern Cape, KwaZulu-Natal, Limpopo, Northern Cape and Western Cape provinces. For Free State province, the effect of a restrictive monetary policy on prices is mixed, depending on the horizon and the quantile involved. Food prices continue to play an important role in the overall inflation dynamics of many countries. For inflation targeting central banks and monetary policymakers in developing and low-income countries in particular, food prices pose even more challenges both from the perspective of achieving inflation targets and the welfare of the many poor households in these economies. In the fourth essay, we look at the stabilizing effect of monetary policy on food inflation in Ghana and South Africa using the quantile regression analysis. For Ghana, we find that monetary policy exerts positive effect on food prices across all the quantiles but the said effect is only statistically significant at the 25th quantile. For South Africa, monetary policy positively influences prices of food and the effect is significant across all the quantiles and prominently at the right tail. Thus, rising food prices in these countries are destabilized even further when monetary policy response is restrictive. On policy front, the relative inflation accommodation on the part of these central banks is deleterious to their credibility and disastrous for anchoring expectations of inflation which is exacerbated by the observed debt constraint. The findings on the operations of the bank lending and interest rate channels provide policy directions for the authorities to exact the required impact on the real economy and inflation in particular. Such policy directions are enhanced by the invaluable information on the heterogeneous regional responses to policy and the colossal role played by food prices in the African setting.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management in the Graduate School of Business Administration, Wits Business School, University of the Witwatersrand, Johannesburg, 2020